2019
DOI: 10.1021/acsomega.9b00312
|View full text |Cite
|
Sign up to set email alerts
|

Novel Colorimetric Method for Simultaneous Detection and Identification of Multimetal Ions in Water: Sensitivity, Selectivity, and Recognition Mechanism

Abstract: Accurate recognition and speciation analysis of heavy-metal ions in complex hydrological environments is always a serious challenge. In this work, we proposed a small-molecule-based ultrasensitive colorimetric detection strategy and successfully applied it to the accurate detection of Fe 2+ , Fe 3+ , Co 2+ , and Hg 2+ in groundwater through the specific recognition of multiple ligands of different metal ions. The detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Many researchers are working in this eld for the development of selective detection of transition and heavy metal ion impurities. From the different available detection methods such as colorimetry, [128][129][130] mass spectrometry, [131][132][133] atomic absorption spectroscopy, 134-136 electrochemical [137][138][139][140] and uorescence 141-145 methods, the uorescence methods are the most reliable and effective because of their high sensitivity, high efficiency, and operative simplicity. Praethong Laopa and Tirayut Vilaivan 40 synthesized cationic polymer-coated ZnO QDs for the selective detection of the Fe(II) ion.…”
Section: Detection Of Metal Ionsmentioning
confidence: 99%
“…Many researchers are working in this eld for the development of selective detection of transition and heavy metal ion impurities. From the different available detection methods such as colorimetry, [128][129][130] mass spectrometry, [131][132][133] atomic absorption spectroscopy, 134-136 electrochemical [137][138][139][140] and uorescence 141-145 methods, the uorescence methods are the most reliable and effective because of their high sensitivity, high efficiency, and operative simplicity. Praethong Laopa and Tirayut Vilaivan 40 synthesized cationic polymer-coated ZnO QDs for the selective detection of the Fe(II) ion.…”
Section: Detection Of Metal Ionsmentioning
confidence: 99%
“…Therefore, the Fe 3+ determination and quantification in these matrices is extremely important to evaluate the metal distribution in the environment. The recommended methods used for this purpose are usually based on spectrophotometry [ 19 ], atomic absorption or inductively coupled plasma spectrometry [ 20 , 21 ], chemiluminescence [ 22 ] and colorimetric [ 23 ] procedures. In many cases, various drawbacks connected to the employment of the mentioned techniques or the use of toxic reagents [ 18 , 24 ], led the scientific community to the development of new methods based on a green chemistry perspective [ 18 ].…”
Section: Mono- and Bis-(3-hydroxy-4-pyridinone) Ligandsmentioning
confidence: 99%
“…The lead ion (Pb 2+ ) is ubiquitous, non-biodegradable, and a highly toxic pollutant that poses serious harm to the ecological environment and global public health. A large number of studies have shown that Pb 2+ has the potential to damage the human nervous system and bone marrow hematopoietic system through various pathways containing air, surface water, and soil. Therefore, the establishment of sensitive and efficient Pb 2+ determination methods is critical for human health and environmental governance. Currently, a multitude of analytical techniques such as fluorescence, electrochemistry, colorimetry, and surface-enhanced Raman scattering (SERS) were applied to determine Pb 2+ . Nonetheless, the application of such technologies is hindered on account of their poor sensitivity and considerable cost. The photoelectrochemical (PEC) analysis, as a burgeoning detection method, possesses lower costs, lower background noise, and higher sensitivity than traditional analysis methods since the generation and output of signals are absolutely separated from each other. , To date, PEC analysis methods have already been commonly adopted to determine proteins, heavy metal ions, small molecules, RNA, and DNA. Therefore, it is expected to build a PEC sensing platform for efficient Pb 2+ detection.…”
Section: Introductionmentioning
confidence: 99%